Nutrition Therapy in Type 2 Diabetic Burn Patient - Ramadhania, Dian Araminta; Wardhana, Aditya; Sinaga, Wina; Wulandari, Yohannessa; Daya, Mulianah; Octovia, Lily Indriani (Lingkar Studi Bedah Plastik Foundation, 2021)
Summary: Severe burn patients experience pronounced metabolic changes that caused hyperglycemia. Other existing metabolic conditions such as diabetes mellitus may worsen this condition. Early, adequate, and personalized nutrition therapy may result in better glycemic control and prognosis.A 44-year-old male with severe burn injury involving 27,5% total body surface area (TBSA) and type 2 diabetes mellitus (T2DM) was given early and diabetes-specific nutrition therapy to meet the recommended energy and protein needs. Lower carbohydrate contents and higher mono-unsaturated fatty acids (MUFA) were components of diabetes-specific nutrition therapy. Desirable blood glucose levels, a positive trend of albumin levels, and reduced inflammatory markers were achieved while being given this nutrition therapy. Sepsis was not diagnosed in this patient. The patient was discharged from the hospital after an improvement in clinical condition. Hyperglycemia commonly occurs in critically ill patients, especially with pre-existing T2DM. The provision of prompt and personalized nutrition therapy will improve clinical outcomes.